A water budget model for operating landfills: An application in Greece. Issue 8 (August 2014) - Komilis, Dimitrios; Athiniotou, Angeliki
The goal of the work was to develop and verify a one-dimensional monthly water budget model (MWBM) to predict leachate generation rates from operating landfills. Although there has been a considerable modelling work on the hydraulic behaviour of landfills after they reach closure, less attention has been given on such modelling for operating landfills that have a continuously changing geometry. A MWBM was developed here that accounted for landfill cell development, precipitation and evaporation, the change of the water holding capacity of a waste cell and waste decomposition. The MWBM was verified using a two-year leachate generation rate database from a new operating sanitary landfill in Greece. The MWBM results showed a very good agreement with field data whilst it was observed that peak precipitation rates followed a parallel trend with peak leachate generation rates. A distinct two-month lag phase between the model results and actual values was observed during a certain period, which is a likely indication of the presence of channelling within the waste mass. A sensitivity analysis performed in the MWBM showed that the leachate is affected by the initial municipal solid waste moisture content as well as by the precipitation rates. A linear regression empirical model showed that precipitation can still be an adequate predictor of leachate generation rates in operating landfills.